2010
DOI: 10.1001/archinternmed.2010.89
|View full text |Cite
|
Sign up to set email alerts
|

Iatrogenic Gastric Acid Suppression and the Risk of Nosocomial Clostridium difficile Infection

Abstract: Increasing levels of pharmacologic acid suppression are associated with increased risks of nosocomial C difficile infection. This evidence of a dose-response effect provides further support for the potentially causal nature of iatrogenic acid suppression in the development of nosocomial C difficile infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
236
3
9

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 399 publications
(256 citation statements)
references
References 45 publications
8
236
3
9
Order By: Relevance
“…Altered gut microbiota in obesity was also observed by other researchers, although the observed changes were usually different (11)(12)(13)(14)(15)(16)(17)(18), and frequently opposite (12)(13)(14)(15)(16)(17)(18) to the observations of Ley et al Note that only three studies stated that the enrolled patients and controls did not take antibiotics in the 3-mo period before sample collection; and all three studies reported an increased Bacteroidetes/Firmicutes ratio in the gut of obese patients (12)(13)(14)19) (Table 1). Our group paid particular attention to proton pump inhibitors and histamine receptor antagonists (14,19) as these agents are known to affect Firmicutes (20). These precautions for patient enrollment gave us confidence in the observed changes in the microbiome of our pediatric NASH patients.…”
Section: Hypothetical Mechanism 1: Elevated Energy Extraction In the mentioning
confidence: 99%
“…Altered gut microbiota in obesity was also observed by other researchers, although the observed changes were usually different (11)(12)(13)(14)(15)(16)(17)(18), and frequently opposite (12)(13)(14)(15)(16)(17)(18) to the observations of Ley et al Note that only three studies stated that the enrolled patients and controls did not take antibiotics in the 3-mo period before sample collection; and all three studies reported an increased Bacteroidetes/Firmicutes ratio in the gut of obese patients (12)(13)(14)19) (Table 1). Our group paid particular attention to proton pump inhibitors and histamine receptor antagonists (14,19) as these agents are known to affect Firmicutes (20). These precautions for patient enrollment gave us confidence in the observed changes in the microbiome of our pediatric NASH patients.…”
Section: Hypothetical Mechanism 1: Elevated Energy Extraction In the mentioning
confidence: 99%
“…[19][20][21] Recent studies have suggested that there is a dose response relationship with administration of PPIs and that risk of Clostridium difficile infection can develop in as soon as three days with PPI therapy. 22,23 Inappropriate administration of high dose PPIs in the ED could place patients at an increased risk for the future development for Clostridium difficile infections later in their hospital course.…”
Section: Discussionmentioning
confidence: 99%
“…Par ailleurs, une étude de cohorte américaine a récemment mis en évi-dence une nette augmentation du risque de colite nosocomiale à C. difficile selon un mécanisme dose-dépendant [22].…”
Section: Infections Gastro-intestinales à Clostridium Difficileunclassified